Wellness eaudiobook A novel. - Hill, Nathan (Books on Tape, 2023)
NEW YORK TIMES BESTSELLER • OPRAH’S BOOK CLUB PICK • AN NPR BEST BOOK OF THE YEAR • The New York Times best-selling author of The Nix is back with a poignant and witty novel about a modern marriage and the bonds that keep people together. Mining the absurdities of contemporary society, Wellness reimagines the love story with a healthy dose of insight, irony, and heart. "A stunning novel about the stories that we tell about our lives and our loves, and how we sustain relationships throughout time—it's beyond remarkable, both funny and heartbreaking, sometimes on the same page.” —NPR When Jack and Elizabeth meet as college students in the gritty '90s Chicago art scene, the two quickly join forces and hold on tight, each eager to claim a place in the thriving underground scene with an appreciative kindred spirit. Fast-forward twenty years to suburban married life, and alongside the challenges of parenting, they encounter the often-baffling pursuits of health and happiness from polyamorous would-be suitors to home-renovation hysteria.    For the first time, Jack and Elizabeth struggle to recognize each other, and the no-longer-youthful dreamers are forced to face their demons, from unfulfilled career ambitions to childhood memories of their own dysfunctional families. In the process, Jack and Elizabeth must undertake separate, personal excavations, or risk losing the best thing in their lives: each other.